Third dose of BNT162b2 improves immune response in liver transplant recipients to ancestral strain but not Omicron BA.1 and XBB - Chang, Zi Wei; Goh, Yun Shan; Rouers, Angeline; Fong, Siew-Wai; Tay, Matthew Zirui; Chavatte, Jean-Marc; Hor, Pei Xiang; Loh, Chiew Yee; Huang, Yuling; Tan, Yong Jie; Neo, Vanessa; Kam, Isaac Kai Jie; et al. (Frontiers in Immunology, 2023)
Vaccine immunogenicity in transplant recipients can be impacted by the immunosuppressive (IS) regimens they receive. While BNT162b2 vaccination has been shown to induce an immune response in liver transplant recipients (LTRs), it remains unclear how different IS regimens may affect vaccine immunogenicity after a third BNT162b2 dose in LTRs, which is especially important given the emergence of the Omicron sublineages of SARS-CoV-2. 95 LTRs receiving single and multiple IS regimens were recruited and offered three doses of BNT162b2 during the study period. Blood samples were collected at day 0, 90 and 180 after the first BNT162b2 dose. At each time point, levels of anti-spike antibodies, their neutralizing activity, and specific memory B and T cell responses were assessed. LTRs receiving single IS regimens showed absence of poor immunogenicity while LTRs receiving multiple IS regimens showed lower levels of spike-specific antibodies and immunological memory compared to vaccinated healthy controls after two doses of BNT162b2. With a third dose of BNT162b2, spike-specific humoral, memory B, and T cell responses in LTR significantly improved against the ancestral strain of SARS-CoV-2 and were comparable to those seen in healthy controls who received only two doses of BNT162b2. However, LTRs receiving multiple IS regimens still showed poor antibody responses against Omicron sublineages BA.1 and XBB. A third dose of BNT162b2 may be beneficial in boosting antibody, memory B, and T cell responses in LTRs receiving multiple IS regimens, especially against the ancestral Wuhan strain of SARS-CoV-2. However, due to the continued vulnerability of LTRs to presently circulating Omicron variants, antiviral treatments such as medications need to be considered to prevent severe COVID-19 in these individuals.